First Report of White Rust Disease Caused by Albugo koreana on Camelina sativa in China - Yang, Hui; Zhao, Zhen Xi; Guo, Ya Xu; Xu, Biao (Plant disease, 2021)
Camelina sativa, an herbaceous annual plant in the family Brassicaceae, is especially well known for its oilseed crop that produce camelina oil (Hovsepyan et al. 2008). In April 2016, white blister rust disease on C. sativa were observed in a cultivated farmland with an incidence of about 60% in Xinyuan County (43°33'39.17"N, 83°14'54.04"E), Xinjiang, China. Symptoms appeared as light-yellow chlorotic spots on the upper surface of the leaves and white blister on the corresponding lower surface. Blister sori were white, oval to ellipsoidal, scattered or coalesce, and 1.8 to 4 mm in diameter. Two representative voucher specimens were deposited in the Mycological Herbarium of Tarim University (HMUT 2527 and HMUT 2528), Aral, China. Sporangiophores hyaline, clavate or cylindrical, straight to slightly curved, (23.7 to) 27.9 to 37.9 (to 42.1) (av. 31) × (7.9 to) 9.6 to 13.7 (to 15.1) (av. 11.4) μm (n = 30), thick-walled on their lower parts, bearing sporangia in chains. Primary sporangia were globose to subglobose, wall equal thickness, and (9.5 to) 10.6 to 13.2 (to 14.3) (av. 11.9) μm in diameter (n = 50). Secondary sporangia were mostly subglobose to ovoid, with a subtruncated base, and (12.1 to) 13.2 to 16.9 (to 18) (av. 15.1) μm × (11 to) 12.1 to 15 (to 16.1) (av. 13.4) μm in size (n = 50). Oogonia were globose to subglobose, (39.7 to) 42.7 to 51.7 (to 54.1) (av. 48.3) μm in diameter (n = 30), irregular. Oospores were globose to subglobose, brown, (34.5 to) 37 to 42.7 (to 45.2) (av. 41.1) μm in diameter (n = 30), 3 to 5 μm wall in thickness, with single warts, 1.5 to 4 × 2 to 3.5 μm (n = 30). The morphological characteristics of specimens were consistent with those of Albugo koreana (Choi et al. 2007). To confirm the identification, genomic DNA were extracted directly from sori on diseased leaves from isolates HMUT 2527 and HMUT 2528, respectively. The internal transcribed spacer (ITS) rDNA and cytochrome oxidase II (cox2) mtDNA were amplified with primers DC6/LR-0 described by Choi et al. (2006) and cox2-F/cox2-R described by Hudspeth et al. (2000), respectively. A BLASTn search revealed that the ITS rDNA sequences (GenBank accession Nos. MW135444 and MW135445) were 99% (838/844 nucleotides)identical to that of A. koreana from Capsella bursa-pastoris (AY929829), and the cox2 sequences (GenBank accession Nos. MW147150 and MW147151) were 100% (567/567 nucleotides) identical to that of A. koreana from C. bursa-pastoris (AY927048). Based on the concatenated ITS and cox2 sequences, Maximum Likelihood and Bayesian analysis showed that pathogen from C. sativa with the reference isolate of A. koreana (ex C. bursa-pastoris) with high bootstrap support values and maximum posterior probability (100 ML BS and 1.00 BPP, respectively). For pathogenicity, sporangia collected from the infected leaves were suspended in sterile water at 4°C for 2 hours to improve zoospore release, and the zoospore suspension obtained from sporangial suspension (1×105 sporangia/ml) was inoculated to the lower surface of six healthy potted plants. Three non-inoculated plants were served as controls. Each plant was kept in a separate plastic humid chamber in a greenhouse with 25°C and 80% humidity for 15 days. Typical symptoms of white rust pustules developed on the inoculated plants were identical to that observed on the originally infected leaves. Control plants remained symptomless.. Based on morphological characteristics, molecular data, as well as pathogenicity tests, the pathogen on C. sativa was identified as Albugo koreana. A. koreana aslo is reported only on C. bursa-pastoris in Korea (Choi et al. 2007; Farr and Rossman 2020). To our knowledge, this is the first record of white rust disease caused by A. koreana on C. sativa, and the species is new to China. This report represents a new host plant association and a new geographical expansion for this species, presenting a potential threat to camelina production in northwest China.